Pengaruh Lagu Tematik terhadap Kecerdasan Musikal Anak Usia Dini di Pendidikan Anak Usia Dini Terpadu Hauriyah Halum - Maryosindra, Wina; Yeni, Indra (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
This research purpose to reveal the thematic songs impact on the musical intelligence of early childhood in Hauriyah Halum Integrated Childhood Education. This research uses quantitative methods with an experimental approach at Hauriyah Halum Integrated PAUD, Padang. The research population involved 51 early childhood children, with a sample of 22 children divided into groups of experimental and control. Data was collected through tests before and after treatment. Analysis for Data used normality, homogeneity, paired sample t-test, and independent sample t-test. The research results showed a significant increase in the intelligence musical of children in the experimental group who received thematic song treatment with a score in average of 18.27 compared to the control group with free song treatment who received an average score of 16.09. Next, reviewing the t-test results obtained a sig (2-tailed) of 0.006. This value is <0.05. So, the final result is that the score is significant